Rewriting white : race, class, and cultural capital in nineteenth-century America - Vogel, Todd, 1959- (Rutgers University Press, 2004)
What did it mean for people of color in nineteenth-century America to speak or write "white"? More specifically, how many and what kinds of meaning could such "white" writing carry? In ReWriting White, Todd Vogel looks at how America has racialized language and aesthetic achievement. To make his point, he showcases the surprisingly complex interactions between four nineteenth-century writers of color and the "standard white English" they adapted for their own moral, political, and social ends. The African American, Native American, and Chinese Americ.